A survey of weed seed contamination of rice paddy in Cambodia. (4th September 2017) - Martin, R J; Van Ogtrop, F; Henson, Y; Broeum, K; Rien, R; Srean, P; Tan, D K Y
Summary: Cambodia has experienced a rapid shift from transplanted to hand broadcast seeded rice, with a consequent increase in seeding rates from 25–30 to 100–200 kg ha −1 . To reduce costs, farmers keep their own seed for sowing with the risk of greater weed seed contamination of the sowing seed. A survey of weed seed contamination in harvested rice paddy was conducted in two provinces of Cambodia (Battambang and Takeo) at the end of the wet season in 2016. Farmers were interviewed about rice‐seeding practices, and a total of 110 farmers' fresh paddy samples were inspected for weed seed contamination from the two provinces. Sowing seed samples collected from 28 seed producer lots and 71 samples of farmer‐kept seed were also analysed for weed seed contamination. In both provinces, the majority of farmers kept their own seed or bought seed from a neighbour. Farm‐kept seed for sowing accounted for 88% of sown seed in Battambang and 89% in Takeo. Seeds of 41 different weed species from 13 plant families were found in the farmers' freshly harvested paddy samples. Overall, farmers managed to reduce the number of weed propagules by 60% and seed producers by 95%. There was no significant difference between farmer‐kept seed and seed producer/seed company seed for the total number of weed seeds present. When shown photos, farmers' rankings of the 10 most common weed species found in freshly harvested paddy did not closely correspond to the actual weed seed frequency in the paddy. When farmers were asked to rank the frequency of weeds in their fields without the option to choose from a list, they ranked the weeds differently. Farmers ranked Ischaemum rugosum, Echinochloa spp. and Fimbristylis miliacea as the three most frequent weed species in their fields. The most frequent weeds in harvested paddy, apart from weedy rice, were I .  rugosum and Melochia corchorifolia . Farmers did not rank M. corchorifolia as a frequently occurring weed, and most farmers could not recognise M. corchorifolia from photographs. The priority for improved seed hygiene is to place the emphasis on assisting farmers to further improve their seed purification techniques and to caution them to inspect seed before purchasing from neighbours, seed producers and seed companies in the absence of the implementation of seed certification regulation.